Analyzing the Effectiveness of Performance Appraisal Systems in Improving Employee Motivation: A Case Study of Kihanga Mparo SACCO in Rukiga District. - Barigye, Augustine (Kabale University, 2024)
The study investigated the effectiveness of performance appraisal systems in improving employee motivation. A case study of Kihanga Mparo Sacco in Rukiga District in Uganda. The study was guided by three objectives which include: identifying various appraisal systems employed by Kihanga Mparo Sacco in Rukiga District, establishing the extent to which the performance appraisal process affects employee motivation in Kihanga Mparo Sacco in Rukiga District, and determining the challenges in appraising employee performance in Kihanga Mparo Sacco in Rukiga District. The researcher adopted a cross-sectional research design method to analyze data. The study revealed that employees and managers jointly set clear, achievable goals that align with SACCO's strategic objectives those clear, measurable objectives are set for each employee at the beginning of the appraisal period. Some respondents to a larger extent showed that when performance appraisals are used to set clear, achievable goals aligned with both individual aspirations and organizational objectives, employees tend to be more motivated. The challenges in appraising employee performance were that bias and subjectivity can lead to unfair appraisals, decreasing employee morale and trust in the appraisal system. There are also managers and supervisors who may lack proper training in conducting performance appraisals effectively. Inadequately trained appraisers may struggle to provide constructive feedback, set realistic goals, and evaluate performance fairly, reducing the overall effectiveness of the appraisal process. The study concludes that the performance appraisal systems at Kihanga Mparo SACCO in Rukiga District have shown to be effective tools in improving employee motivation. By setting clear goals, providing constructive feedback, recognizing achievements, and ensuring fairness, these systems contribute significantly to a motivated and engaged workforce. However, addressing the identified challenges and continuously refining the appraisal process will further enhance its effectiveness. The study recommends that there is a need to perform a thorough review of the current appraisal systems in place by engaging HR professionals to document all appraisal methods currently used. A detailed inventory of appraisal systems, including performance appraisals, 360-degree feedback, management by objectives (MBO), key performance indicators (KPIs), balanced scorecards, and peer reviews